PERANCANGAN DAN PENGUJIAN ALAT PENGASIN TELUR BEBEK DENGAN AIR COMPRESSION PRESSURE - Rohmat, Yusup Nur; Hidayat, Kusnandar; Canra, Delffika; Suliono, Suliono; Haryadi, Haryadi; Priyatna, Hendar (Politeknik Negeri Sriwijaya, Indonesia, 2021)
The traditional method of making salted eggs usually using the salting, which is done well, its needs time about 14 days. This condition indicated to have a method that can speed up the process of salting the eggs. The process of salting eggs normally uses the usual soaking method where the eggs are coated with bricks and rubbing ash then left to stand. The diffusion of salt penetration in traditional salting takes place slowly. For this reason, the speed of salt penetration can be done by increasing the salt level in the soaking solution so that the penetration of salt into the eggs can take place faster. This methodology in this research study using of air pressure to speed up the process of salting the eggs. The method used is to use air pressure with the use of compressor air pressure at a pressure of 4 - 6 Bar with a salting test time of about 4 to 7 hours